TREATMENT OUTCOMES OF PROXIMAL GASTRIC CANCER DEPENDING ON THE EXTENT OF SURGICAL RESECTION - M. O. Maksimov; S. A. Tuzikov; G. N. Strizhakov; E. O. Rodionov (Сибирский онкологический журнал)
Surgical resection for proximal gastric cancer remains an important problem of oncology. Personalized surgical management represents one of the main challenges in treating gastric cancer. The aim of the study was to analyze surgical outcomes of proximal gastric cancer depending on the tumor spread, extent of surgery and the presence of intraperitoneal free cancer cells. Material and Methods. The study included 68 patients with morphologically verified locally advanced proximal gastric cancer. The patients were divided into 2 groups. Group I consisted 37 patients, who underwent total gastrectomy of 31 patients; Group II comprised who underwent proximal subtotal gastrectomy. Results. The overall three-year survival was 48.7 ± 16.9 % in Group I and 66.4 ± 13.2 % in Group II patients. The 3-year progressive-free survival rate was 51.5 ± 18.5 % after proximal subtotal gastrectomy and 34.8 ± 25.6 % after total gastrectomy. The presence of tumor cells in the abdominal cavity was proven to lead to early carcinomatosis. Thus, the 2-year overall survival rate was 26.7 ± 42.8 % in patients in whom free cancer cells were found in peritoneal washings and 69.8 ± 9.0 % in patients with negative cytology findings from washings. Conclusion. Proximal subtotal gastrectomy provides better survival rates compared to total gastrectomy in patients with locally advanced proximal gastric cancer. Local spread of the tumor, which is known to significantly increase the risk of lymph node metastasis and contamination of the peritoneal cavity with cancer cells, is one of the main unfavorable prognostic factors.